Effect of Stone-wales and Vacancy Defect in Double Walled Carbon Nanotube for Mass Sensing. (2016) - Patel, Ajay M.; Joshi, Anand Y.
Abstract: This paper deals with studying the mass sensing characteristics of defective Double Walled carbon Nanotubes (DWCNTs) using a molecular structure mechanics approach. In this study, vibrational behavior of defective DWCNTs are studied. Two types of defects i.e. Stone-Wales (S-W) and vacancy defects with different location are considered in the present investigation. The interlayer separation in the form of Van der Waals interaction is modelled using characteristic spring element. The inner and outer walls of the nanotube are modelled as elastic beams with a spring element connecting the two layers. Two types of boundary conditions, i.e. cantilever and bridged are considered for the purpose of analysis. In this paper, the effect of S-W defect and Vacancy defect of armchair, zigzag and chiral Double-walled carbon nanotubes (DWCNTs) was studied using an atomic- finite element model based on Molecular Structural Mechanics approach. It is observed that for all three types i.e. Armchair, Zigzag and Chiral nanotubes, the effect of both the type of defect is maximum when it is nearer to the fixed end. The model has been validated with the existing literature.